2021
DOI: 10.1002/cam4.4317
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a glycolysis‐related gene signature for survival prediction of ovarian cancer patients

Abstract: Background Ovarian cancer (OV) is deemed the most lethal gynecological cancer in women. The aim of this study was to construct an effective gene prognostic model for predicting overall survival (OS) in patients with OV. Methods The expression profiles of glycolysis‐related genes (GRGs) and clinical data of patients with OV were extracted from The Cancer Genome Atlas (TCGA) database. Univariate, multivariate, and least absolute shrinkage and selection operator Cox regression analyses were conducted, and a progn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 114 publications
0
19
0
Order By: Relevance
“…IRS2, ANGPTL4, TGFBI, LHX9, PC, and DDIT4 [ 23 ]. Zhou et al identified a DNA methylation-driven genes signature, including PON3, MFAP4, AKAP12, and BHMT2 [ 24 ].…”
Section: Exploring Clinical Benefit Of Signaturementioning
confidence: 99%
“…IRS2, ANGPTL4, TGFBI, LHX9, PC, and DDIT4 [ 23 ]. Zhou et al identified a DNA methylation-driven genes signature, including PON3, MFAP4, AKAP12, and BHMT2 [ 24 ].…”
Section: Exploring Clinical Benefit Of Signaturementioning
confidence: 99%
“…The results were also exciting: in the C-index for predicting the TCGA cohort, the risk signature of our study showed better predictive value than the glycolysis-related gene signature established by Zhang et al. ( 34 ), the glycolysis-related lncRNA signature established by Zheng et al. ( 35 ), and the DNA methylation-driven gene signature established by Zhou et al.…”
Section: Resultsmentioning
confidence: 57%
“…TGCA database is also widely used in oncology studies; it is a pan-cancer project hosted by the National Institutes of Health (NIH), providing a wide variety of tumors and different molecular data types that can be downloaded and analyzed. In the past few years, most studies have focused on RNA sequencing (RNA-Seq) analysis, such as mRNA and non-coding RNAs [ 12 15 ]. Recently, following the updating of old algorithms and the discovery of new ones, CIBERSORT, MCPcounter, and other algorithms have been used to assess tumor immune cell infiltration.…”
Section: Introductionmentioning
confidence: 99%